Strategies for integrating quality, environmental, safety and health management systems - Mohammad, Musli (Trans Tech Publications Inc, 2013)
This paper discusses the strategies for integrating Quality, Environmental, Safety and Health Management Systems based on survey and case studies results. Questionnaires were distributed to 87 companies that certified with both ISO9001 and ISO14001. Meanwhile, three case studies were conducted at the manufacturing companies that have integrated several management systems. There are two ways of integrating the management systems which are: (1) consecutive implementation of management systems followed by integration or (2) integrate the management systems simultaneously from the beginning. Based on survey and case studies, it was found that many organisations started with implementing individual management system first, and then followed by integrating the management systems. Almost all the survey respondents agreed that the sequence should start with establishing Quality Management System first, and then integrate with Environmental Management System and followed by Occupational Health and Safety Management System.